2021
DOI: 10.1038/s41596-020-00462-5
|View full text |Cite
|
Sign up to set email alerts
|

Detection of aberrant gene expression events in RNA sequencing data

Abstract: RNA sequencing (RNA-seq) has emerged as a powerful approach to discover disease-causing gene regulatory defects for individuals affected with a genetically undiagnosed rare disorder. Pioneer studies have shown that RNA-seq could increase diagnostic rates over DNA sequencing alone by 8% to 36 % depending on disease entities and probed tissues. To accelerate the adoption of RNA-seq among human genetic centers, detailed analysis protocols are now needed. Here, we present a step-by-step protocol that instructs how… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
95
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 89 publications
(96 citation statements)
references
References 63 publications
1
95
0
Order By: Relevance
“…Transcriptome sequencing (RNA-seq) is deemed to enhance identifying Mendelian variants by ~10-30% (Kremer et al, 2017;Gonorazky et al, 2019). Allelic imbalances in transcriptomics data can identify imprinting, uni-parental disomy, and X chromosome inactivation (Gonorazky et al, 2019;Yépez et al, 2021). However, the tissue transcriptome does not necessarily reflect the proteome, metabolome, and phenome (Wang et al, 2019).…”
Section: Remaining Challengesmentioning
confidence: 99%
“…Transcriptome sequencing (RNA-seq) is deemed to enhance identifying Mendelian variants by ~10-30% (Kremer et al, 2017;Gonorazky et al, 2019). Allelic imbalances in transcriptomics data can identify imprinting, uni-parental disomy, and X chromosome inactivation (Gonorazky et al, 2019;Yépez et al, 2021). However, the tissue transcriptome does not necessarily reflect the proteome, metabolome, and phenome (Wang et al, 2019).…”
Section: Remaining Challengesmentioning
confidence: 99%
“…Expression outliers are defined as the gene-sample combinations with an FDR ≤0.05, resulting in a handful of outliers per sample, depending on the number of samples. In a subset of GEUVADI's cohort (Lappalainen et al, 2013) comprising 100 control samples from different sequencing centers (CNAG CRG, N 31; ICMB, N 28; and UNIGE, N 41) and ancestries (British, N 12; Finnish, N 26; Tuscan, N 22; Utah, N 16; and Yoruba, N 24), OUTRIDER's denoising autoencoder was able to control for covariation (Yépez et al, 2021b). The sample size of each subgroup was relatively similar; therefore, the autoencoder is yet to be tested in cases where a subgroup is substantially underrepresented.…”
Section: Aberrant Expressionmentioning
confidence: 99%
“…Application of FRASER in the rare disease cohort from Kremer et al (2017) identified all three previously detected pathogenic splicing aberrations, plus an intron-retention event missed by LeafCutter, and a synonymous variant causing a splice defect missed by Kremer et al (Mertes et al, 2021). FRASER was also applied to the GEUVADIS multicenter and multi-ancestry cohort and was able to remove sample covariation for all metrics (Yépez et al, 2021b). In addition, FRASER has been used by Murdock et al (2021) leading to the diagnosis of four out of 78 subjects and by Yépez et al (2021a) leading to the diagnosis of 19 (12 in combination with aberrant expression) subjects from various ancestries.…”
Section: Splicing Outliersmentioning
confidence: 99%
See 2 more Smart Citations